Contribution to the knowledge of the scale insects (Hemiptera Coccoidea) from the Aosta Valley (Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
The paper presents the results of a survey on the scale insect faunacarried out over different years in the Alpine Aosta Valley (Italy). A total of 54species have been collected in this Italian region. Of these, 7 are new for theItalian fauna: Neomargarodes festucae Archangelskaja, Chaetococcus sulci(Green), Peliococcus marrubii (Kiritshenko), Rhodania porifera Goux, Eriococcusplacidus Green, Rhizopulvinaria saxatilis Canard and R. spinifera Borchsenius.Two other species previously recorded from the Aosta Valley as Rhizoecus caesiiSchmutterer and Mirococcopsis nagyi Kozar proved their pertinence respectivelyto Rhizoecus pratensis Borchsenius & Tereznikova and Volvicoccus volvifer Goux.The opportunity is taken to synonyrnize Antoninella inaudita Kiritshenko, 1938,n. syn. with Antoninella parkeri (Balachowsky, 1936) n. comb. The peculiarclimate of the Aosta Valley allows the establishment of several thermophilous orxerophilous species, some of which are considered rare species, such as Neomargarodesfestucae, Antoninella parkeri, Chaetococcus sulci, Rhizoecus albidusGoux, Rhodania porifera, Peliococcus marrubii, Volvicoccus volvifer, Cerococcuscycliger Goux, Rhizopulvinaria artemisiae (Signoret), R. spinifera, Quadraspidiotuslabiatarum (Marchal).
Keywords: Coccoidea; new combination; new synonym; faunistic survey; Italy; Alps